2018
DOI: 10.1002/clc.23069
|View full text |Cite
|
Sign up to set email alerts
|

Associations of ideal cardiovascular health with GlycA, a novel inflammatory marker: The Multi‐Ethnic Study of Atherosclerosis

Abstract: Background: Unhealthy lifestyles and inflammation contribute to cardiovascular disease (CVD). GlycA is a novel biomarker of systemic inflammation representing posttranslational glycosylation of acute phase reactants and associated with increased clinical CVD risk. Hypothesis: We hypothesized that ideal cardiovascular health (CVH), as assessed by (higher) Life’s Simple Seven (LS7) scores, would be associated with lower GlycA levels among individuals free of CVD in a multi-ethnic community-based population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…(OR = 1.79, 95% CI = [1.48, 2.18], P = 3.79 × 10 −9 ), which was consistent with a previous follow-up study 20. This positive association was further validated when the model was further adjusted for covariates (OR = 1.86, 95% CI = [1.54, 2.32], P = 2.91 × 10 −9 ).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…(OR = 1.79, 95% CI = [1.48, 2.18], P = 3.79 × 10 −9 ), which was consistent with a previous follow-up study 20. This positive association was further validated when the model was further adjusted for covariates (OR = 1.86, 95% CI = [1.54, 2.32], P = 2.91 × 10 −9 ).…”
supporting
confidence: 86%
“…As previous reported, metabolic biomarkers always play a critical role in CVD. 20 Hyperglycemia, as measured by HbA1c level, is confirmed as an independent risk factor for CVD, and leads to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…LS7 scores were categorized into CVH groups classified as "optimal" (12-14, "average" (8-11), or "inadequate" (0-7). GlycA was independently inversely associated with continuous LS7 scores [176].…”
Section: Apparently Healthy Populationsmentioning
confidence: 91%
“…GlycA has been measured in apparently healthy individuals from large population studies such as WHS, 'Justification for the Use of Statins in Primary Prevention: An Intervention Trial Evaluating Rosuvastatin' (JUPITER) trial, and MESA. In all of them, elevated baseline circulating glycoprotein N-acetyl methyl groups were associated with longitudinal risk of CVD incidence and mortality, among other pathologies such as chronic inflammatory-related severe hospitalization, cancer, or death [106,108,175,176]. Considering the results, the authors defend GlycA's role as an important predictor of 5 to 15-year risk of CVD [107,108].…”
Section: Apparently Healthy Populationsmentioning
confidence: 94%
“…Cardiovascular and cardiometabolic mortalities were associated with arabinogalactan protein 1 (AGP1), C-type lectin domain family 3 member B (CLEC3B; tetranectin), cystatin-C, kallikrein B1 (KLKB1), insulin-like growth factor 1, N-terminal pro-b-type natriuretic peptide, peripheral myelin protein 2 (PMP2), soluble receptor for advanced glycation end products (sRAGE), and uncarboxylated matrix Gla protein (UCMGP) (168). Studies in a multi-ethnic cohort revealed a positive association between glycosylated acute phase protein (GlycA: a novel biomarker of systemic inflammation) and suboptimal cardiovascular health (169). Study results indicated that GlycA, derived from glycosylation of major acute inflammatory proteins and a stable biomarker of systemic inflammation compared to other markers (167,170) could be deployed for biomonitoring populations that have different lifestyles (dietary preferences, smoking etc.)…”
Section: Proteomicsmentioning
confidence: 99%